Hodgetts + Fung : scenarios and spaces - Forster, Kurt Walter; Forster, Kurt Walter (New York : Rizzoli International Publications, 1997)
The Supercalifragilistic architecture of Hodgetts + Fung / Kurt W. Foster -- Gritty pomp: toward a new humanism -- Southside Settlement Community Center -- Competition for Roosevelt Island -- Hudson Wilcox Mixed-Use Development -- Gagosian House and Gallery -- Viso House -- Towell Library, University of California at Los Angeles -- "Blueprints for modern living," exhibition design -- Los Angeles Arts Park -- Venice Interarts Center -- Seoul Summer Olympics Athletes' and Reporters' Village -- Craft and Folk Art Museum -- Parts and wholes: product and module -- Franklin/La Brea Housing -- Hemdale Film Corporation and Office Facility -- Linc Housing System -- Creative Playthings Retail Shop -- Airframe Aluminum Furniture -- Towell Library, University of California at Los Angeles -- Punch-out cardboard furniture -- Rough tech: decoding the ordinary -- Five Shrines, Installation -- Southside Settlement Community Center -- Towell Library, University of California at Los Angeles -- Skinner's Room, "Visionary San Francisco" Installation -- Experience and scenario -- "Blueprints for modern living: history and legacy of the case study houses," exhibition design -- Invited competition, expansion plan for the Universal Amphitheater -- Invited competition, Vesey Place -- Rockplex Entertainment Center -- AST Computers, exhibition design -- A place for encounter -- Invited competition, Los Angeles Arts Park -- Villa Linda Flora -- Ecotopia, conceptual design -- The River and the City, Nicollet Island, Minneapolis -- UCLA Gateway,University of California at Los Angeles -- "Blueprints for modern living," exhibition design -- Tokyo Theme Park, Gate II Main Street -- Third Street Promenade Planning Study -- Competition for Roosevelt Island -- The Imploding Building -- Click & Flick Agency -- Cookie Express, retail prototype -- Print Salon -- Microshop: Interactive Kiosk -- Villa Linda Flora -- Built-in life cycle: all buildings are temporary -- Towell Library, University of California at Los Angeles -- Domore Showroom -- Zip Chip Technology -- "The Magic of Play," exhibition design -- 00:00, a Mobile Theater, prototype -- List of projects -- Exhibitions/Installations -- Awards -- Select bibliography -- Biographies -- Photography credits.
Includes bibliographical references (pages 161-164).
Keywords: Hodgetts + Fung (Firm); Architecture -- History -- 20th century -- United States